2007
DOI: 10.1097/01.prs.0000260712.44089.e7
|View full text |Cite|
|
Sign up to set email alerts
|

Autologous Fat Transfer for Facial Recontouring: Is There Science behind the Art?

Abstract: Although there is an increased trend in replacement of soft-tissue volume with autologous fat transfer, the literature fails to provide definitive evidence of fat survival. A large-scale clinical assessment using three-dimensional volumetric imaging would provide useful outcome data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(119 citation statements)
references
References 55 publications
1
109
0
8
Order By: Relevance
“…From Coleman's technique, different approaches for fat harvesting, processing, and injection were suggested for improving the cosmetic outcome and graft survival. [22][23][24][25][26][27][28] Recently, immunohistochemical studies of the extracellular matrix of the lipoaspirate showed the presence of adipose-derived stem cells. [17][18][19] For its volumetric qualities and regenerative capacity, fat harvesting was suggested in many facial asymmetries: after trauma, post-tumor resection, congenital complex, and hemifacial asymmetry (Franceschetti and Romberg syndromes).…”
Section: Discussionmentioning
confidence: 99%
“…From Coleman's technique, different approaches for fat harvesting, processing, and injection were suggested for improving the cosmetic outcome and graft survival. [22][23][24][25][26][27][28] Recently, immunohistochemical studies of the extracellular matrix of the lipoaspirate showed the presence of adipose-derived stem cells. [17][18][19] For its volumetric qualities and regenerative capacity, fat harvesting was suggested in many facial asymmetries: after trauma, post-tumor resection, congenital complex, and hemifacial asymmetry (Franceschetti and Romberg syndromes).…”
Section: Discussionmentioning
confidence: 99%
“…In early 2007, Kaufman MR et al reported no evidence of the post autologous fat grafting fat survivability and the predictability of volume restoration. In conducting a quantitative study using large-scale clinical assessment and three-dimensional volumetric imaging to provide useful outcome data, they found that fat survival of autologous fat graft in that period is questionable [21]. By contrast, a rapid growth of new procedures used to collect larger amounts of transplantable fatty tissue by using liposuction (e.g., water-assisted liposuction); and the procedure of autologous lipo-transplantation after tissue separations.…”
Section: Discussionmentioning
confidence: 99%
“…However, resorption of fat transplanted has been reported (Sommer & Sattler, 2000;Masuda et al, 2004;Kaufman et al, 2007) and current efforts focus on identifying methods that may minimize this undesirable result. There is no universal agreement on what constitutes an ideal methodology to obtain better graft takes and results.…”
Section: Autologous Fat Graftsmentioning
confidence: 99%